1998
DOI: 10.1103/physrevlett.81.550
|View full text |Cite
|
Sign up to set email alerts
|

New Molecular Collisional Interaction Effect in Low-Energy Sputtering

Abstract: An unexpected pronounced enhancement is observed in sputtering yields per atom for N 1 2 compared to N 1 from a polycrystalline gold target. This effect is seen when the kinetic energy per projectile atom is below 500 eV and increases as projectile energy decreases to near-threshold energies. We report on the first observations of a pronounced enhancement in sputtering yields for molecular ions as compared to atomic ions at low projectile energies near sputtering thresholds (30 -500 eV) [1]. At high energies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Due to its low chemical reactivities, an Au surface can be easily maintained in a very clean state in ultra high vacuum conditions, which allows one to measure various physical properties of the Au surface with relative ease. The sputtering yield, for example, is one of the most fundamental physical quantities and the Au sputtering yields by noble gas ions have been extensively studied especially in the energy range above 1 keV [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. On the other hand, sputtering yields of Au by noble gas ions [8,9,11,[13][14][15][16][17][18] or self-sputtering yields of Au [19][20][21] in the energy range below a few hundred electronvolts have not been reported to the same degree of extensiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low chemical reactivities, an Au surface can be easily maintained in a very clean state in ultra high vacuum conditions, which allows one to measure various physical properties of the Au surface with relative ease. The sputtering yield, for example, is one of the most fundamental physical quantities and the Au sputtering yields by noble gas ions have been extensively studied especially in the energy range above 1 keV [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. On the other hand, sputtering yields of Au by noble gas ions [8,9,11,[13][14][15][16][17][18] or self-sputtering yields of Au [19][20][21] in the energy range below a few hundred electronvolts have not been reported to the same degree of extensiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of a thermal dependence could provide more definitive information, as reactivity is a strong function of temperature (Roth, 1983). Irradiation by diatomic molecular ions such as H 2 + have been shown to increase the sputtering from surfaces at high energies (>10 keV) due to overlapping of collision cascades; similarly, at energies <1 keV the sputtering yield deviates from twice the monatomic yield due to variation in the molecule effective mass (Dobes et al., 2011; Yao et al., 1998). However, low‐energy ion scattering measurements for 2 keV H 2 + and microbalance analysis for 2, 4 keV O 2 + have shown that for singly ionized diatomic molecules, the kinetic energy is divided quite equally between atoms (Dukes et al., 1999; Szabo et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These findings agree with previous studies on the comparison between sputtering by atomic and molecular ions at kinetic energies in the keV range. Molecular sputtering effects have been reported for two energy regimes (Andersen & Bay, 1974, 1975; Dobes et al., 2011; Yao et al., 1998). For slow molecular ions with energies below about 1 keV/atom, it cannot be assumed that the molecule immediately dissociates upon impact.…”
Section: Discussionmentioning
confidence: 99%